Poor knowledge of anemia and sexually transmitted disease but better knowledge of HIV/AIDS among unmarried adolescents aged 15-24 years (Universa Medicina, 2021)
BACKGROUND Basic knowledge of sexual and reproductive health is important to be introduced during the premarital period, to reduce high-risk sexual behavior among adolescents, as well as to increase the correct attitude in their future marriage. This study explored the knowledge of HIV/AIDS, sexually transmitted diseases (STDs) and anemia among unmarried adolescents.METHODS This was a cross-sectional analytical study on secondary data from the Indonesian Demographic and Health Population Survey 2017, initially conducted by the National Population and Family Planning Board (BKKBN). Knowledge of HIV/AIDS, STDs and anemia among unmarried adolescents aged 15-24 years in West Java Province and Jakarta, the capital city of Indonesia, was compared and analyzed using the chi-square test.RESULTS In total, 5,389 weighted data were retrieved. In general, adolescents in Jakarta had better knowledge of all diseases compared to those in West Java (p